If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -15y = 23 Combine like terms: -2y + -15y = -17y -17y = 23 Solving -17y = 23 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-17'. y = -1.352941176 Simplifying y = -1.352941176
| 4x+2x-6=4(x-3)+7 | | 2x-1/4x=4/6 | | 3b^2-7b-2=0 | | (5z+2)(6-z)=0 | | X/2-1/4=20 | | y-9=55 | | 13+x-7=-2-3x | | (5x-12)+2x=20+x | | (2x+8)(3x-2)= | | m^2+15=8m | | 14m+n-6m+9n= | | 15-x(3)+2x=20 | | B=p+4a+3c | | x+x-2x+4x-1=4-x | | 7x+9(1-2x)=4-7(x-1) | | B=p+4a+33c | | 3b+2b-2=13 | | 3x-17+2x+1=25-x | | 3x-17+2x+1=25 | | 18+3(90-x)=90 | | x-49=8 | | s(t)=5t^2+15t | | (9x+4)-(-9x+8)= | | 77/11(5-3) | | 2[x+6]=2[-x+6.5] | | 4x+5=3x-14 | | x(4+3)=5-8x | | -4a=14a-12[4a+10] | | (x+7)(5)=45 | | -3[2u+5]+3.5u=-1u | | 100-50/5•10 | | f(7)=8x-3 |